Like terms have the same variable (or have no variable). In this expression you have two sets of like terms: Those with x, and those with y
Those with x: 5x, -x, 2x
Add the coefficients: (5-1+2)x = 6x
Those with y: 7y, -2y
Add the coefficients: (7-2)y = 5y
6x+5y is the answer.
Hope this helps.
2006-11-27 06:54:32
·
answer #1
·
answered by Aegor R 4
·
0⤊
0⤋
Rearrange the values:
5x+2x-x+7y-2y
6x+5y
2006-11-27 07:00:29
·
answer #2
·
answered by Anonymous
·
0⤊
0⤋
5x + 7y - x - 2y + 2x
(5-1+2)x+(7-2)y
6x+5y
2006-11-27 07:04:09
·
answer #3
·
answered by yupchagee 7
·
0⤊
0⤋
First get together all the like terms
(5x-x+2x)+(7y-2y)=
6x+5y
2006-11-27 09:13:57
·
answer #4
·
answered by lulu 3
·
0⤊
0⤋
5x+7y-x+2x=
5x-x+2x= 6x
7y-2y=5y
so the answer is 6x+5y
2006-11-27 07:00:00
·
answer #5
·
answered by dirrtybaster19 1
·
0⤊
0⤋
5x + 7y - x - 2y + 2x = 6x + 5y
QED
2006-11-27 06:58:15
·
answer #6
·
answered by CSUFGrad2006 5
·
0⤊
0⤋
rearrange equation:
5x+2x-x-2y+7y
now add/subtract all x's and y's
=> 5x+2x=7x-1x=6x
=> -2y+7y=5y
answer: 6x+5y
2006-11-27 07:00:47
·
answer #7
·
answered by sarah2mee 1
·
0⤊
0⤋
Combine like terms (x's to x's & y's to y's):
6x + 5y
2006-11-27 06:55:32
·
answer #8
·
answered by Dave 6
·
0⤊
0⤋
6x + 5y
2006-11-27 06:59:30
·
answer #9
·
answered by Raven_419 2
·
0⤊
0⤋
6x +5y
2006-11-27 06:54:31
·
answer #10
·
answered by rewrite_h35 2
·
0⤊
0⤋